Training needs for Teaching Staff Members of Higher Studies in Faculty of Arts, Misurata University According to e-learning Requirements - Algazal, Mohamed Omar; Saad, Nabila Bileed ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2020)
The research aims to identify the actual needs of members of the teaching staff in postgraduate studies at the Faculty of Arts Misurata University. According to the e-learning environment, and to achieve the goal of the research, the researchers prepared and developed a questionnaire as a study tool that included five areas, and the validity and reliability of the tool was verified, The results showed that. 1.There are training needs for the faculty members in the e-learning environment in the field of computer use and benefit from modern technologies in classrooms. 2.The use of the Internet information network in teaching. 3.The use of modern technologies in communicating with others scientifically and the methods used to develop electronic skills. 4.There are no statistically significant differences at the level of significance (0.05) in the responses of the research sample according to the variable of the academic degree and years of educational experience in teaching and variable of the training courses according to electronic educational environment.